Compendio nacional de estadísticas de recursos hídricos 2018 - Autoridad Nacional del Agua (2019)
Equipo técnico: Dalila Zulema Navarro Ruíz, Gustavo Adolfo Palomares Córdova, Christian De La Torre Mayta, Luz Áyde Carrillo Moscoso, Edwin Zenteno Tupino, Jeanne Susan Quiñonez Rojas, Víctor Antonio Huapaya Avalos, Gloria Soledad Aguilar Rivera, Judith Shirley Mariñas Adrianzen, Víctor David Godoy Jiménez, Homero Roosevelt Guerrero Aranda, Alex Favio Paco Narváez, Luis Alberto Torres Obando, Julio César Oyola Loayza, Eric Edilberto Aliaga Romayna, César Luque del Carpio, Alex Juvenal Huarancca Villasante, Silvia Sachiko Ramos Tamayo, Litzia Nidia Cisneros, Huamaní, Lucy Julca De La Cruz, Juan Pablo Mariluz Silva, Benjamín Roisy Molina Chávez, Jean Carlo Céspedes Reátegui.